Efektivitas Penyaluran Pupuk Bersubsidi Bagi Petani Padi Di Desa Langi Kecamatan Bontocani Kabupaten Bone - Ramlayana, Ramlayana; Ansari, Muh Isa; Sudarmi, Sudarmi (Universitas Muhammadiyah Makassar, 2020)
This study purposed to detrmine the effectiveness of the distribution of subsidized fertilizer for rice farmers in Langi Village, Bontocani District, Bone Regency. This study used qualitative research. The number of informants was 7 people. data collection techniques used Observations, interviews and documentation. Data analysis techniques were data reduction. Data reduction, data presentation, verification of qualitative data. The results of this study showed that the effectiveness of the distribution of subsidized fertilizer for rice farmers in Langi village, Bontocani District, Bone Regency was quite good, but some were effective and some were not effective. This was seen from the indicators (1) Exactly the type was effective because in the RDKK concept stated farmer who submitted or ordered various types of fertilizers in developing his farming business. (2) Exact amount was effective because it was based on the area of land of farmers who were trying to farm in the fields. (3) Right Price had not been effective because there were additional costs for farmers so that prices had not increased according to HET. (4) Punctuality was not effective yet because distribution was often experiencing delays.